ANALISIS PENDAPATAN DAN KELAYAKAN INDUSTRI KERIPIK SUKUN PADA RUMAH INDUSTRI CITRA LESTARI PRODUCTION DI KOTA PALU - Kibar Kibar; Lien damayanti (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
In Palu City, quite a number of industries use breadfruit as the main raw material in their production. Based on the research results, the Citra Lestari Production Industry is one of the industries in Palu City that produces breadfruit chips in several industries in Palu City. Agro-industry is an effort to increase the efficiency of the agricultural sector to become a very productive activity through the process of agricultural modernization. This study aims to, analyze the amount of costs, revenues, and income at the Citra Lestari Production Industrial house in running the breadfruit chips business. Knowing the feasibility of home breadfruit chips Industry Citra Lestari Production. This research will be conducted at the Citra Lestari Production Industry house in Palu City, having its address at Jl. Kimaja No. 9 Sub-district of West Besusu, East Palu District. The location was determined purposively with the consideration that the Citra Lestari Production industrial house is a chipprocessing industry in the city of Palu. This research was conducted in August-September 2019. Respondents in this study were leaders and workers of the Citra Lestari Production Industry. Respondents were determined purposively, with the consideration that company leaders know the ins and outs of the company, such as the company's history, production capacity, financial condition, and so on. Thus the number of respondents consists of 1 leader and 1 worker. The data used in this study came from primary data and secondary data. Primary data collection was carried out by means of observation and direct interviews with the leadership and home workers of the Citra Lestari Production Industry house using a questionnaire, and secondary data was obtained from various literatures and several related agencies that could support this research activity. Based on the results of the research and discussion that has been described, it can be concluded as follows. The results showed that the production of breadfruit chips was 3,000 packs/150 grams at a price of Rp.13,000/package, so that the total revenue to the Citra Lestari Production industry was Rp.30,000,000/month. It is known that the fixed costs are Rp.9,408,082/month, while the total variable costs incurred is Rp.4,299,500/month. So the total costs incurred by the Citra Lestari Production Industry Rp.13,707,582/month with an income of Rp.30,000,000 minus the total cost of Rp.13,707,582 is Rp.25,292,418/month. The comparison of the total amount of revenue with the total cost is known to be Rp.39,000,000, while the total cost incurred by the Citra Lestari Production Industry house is Rp.13,707,582, thus the R/C value of the Citra Lestari Production Industry house is 2.84.